Serological risk factors for concomitant interstitial lung disease in patients with idiopathic inflammatory myopathy. (April 2020) - Huang, Hung-Ling; Lin, Wen-Chih; Yeh, Che-Chun; Sun, Yuan-Ting
Highlights: High mortality of coexistence of ILD in patients with IIM. Patients with interstitial lung disease had lower initial creatine kinase levels. Patients with anti-Ro52 antibodies had 9.17-fold increased odds of ILD. Patients with anti-Ro52 or anti-Jo1 antibodies had 13.44-fold increased odds of ILD. The common serology tests can guide pulmonary screening for patients with IIM. Abstract: Interstitial lung disease (ILD) is an extramuscular manifestation associated with increased mortality in idiopathic inflammatory myopathy (IIM). To identify risk factors for ILD in patients with IIM, this study retrospectively enrolled 117 eligible patients from a university medical center. After a comprehensive chart review, 56 patients were stratified into ILD (n = 28) and non-ILD (n = 28) groups. Clinical features, laboratory data, concomitant diseases, and serology profiles were compared. Patients with ILD had high prevalence of anti-Jo1 antibodies ( p = 0.002), anti-Ro52 antibodies ( p < 0.001), both anti-Jo1 and anti-Ro52 antibodies ( p = 0.008), anti-Jo1 or anti-Ro52 antibodies ( p < 0.001), and lower initial creatine kinase (CK) levels ( p = 0.006). Moreover, patients with anti-Ro52 antibodies and either anti-Ro52 or anti-Jo1 antibodies had 9.17-fold (95% confidence interval [CI]: 2.858–33.487, p < 0.001) and 13.44-fold (95% CI: 4.008–52.757, p < 0.001) increased odds of developing ILD, respectively. By contrast, patients with higher CK levels had 0.99-fold (95% CI: 0.999–0.999, p = 0.011) increased odds of developing ILD. Both anti-Ro52 and anti-Jo1 antibodies were independent serological risk factors for IIM-associated ILD. Because these serology tests are commonly available, they can be used to guide pulmonary screening for patients with IIM to increase neurologist proactivity in recognizing and treating extramuscular conditions.